EIDOS E PROBLEMA SEMANTICO NELL'ESTETICA DI WŁADYSŁAW STRÓŻEWSKI. OSSERVAZIONI IN MARGINE ALLA RACCOLTA DI SCRITTI "INTORNO AL BELLO" - cl, redakcja (Colloquia Litteraria, 2020)
In this paper, I argue that Stróżewski sees the meaning of artwork in getting closer the essence of things, in grasping their eidos (of their ideal Gestalt), in a specific, Platonic sense. Stróżewski's theory could, therefore, justify not only the representational forms of art, but also the "pure" objects and colours of abstract art, and even the very optical structure of new art media. On the other hand, his objectivist approach to beauty as an ontological value is at odds with a pragmatic view of the relationship between artwork and receiver, as shown by the disagreement with Roman Ingarden.